Celebrate Nation, Commemorate History, Embody the Estado Novo: The Exhibition of the Portuguese World (1940) - Gori, Annarita (2019)
In 1940, the Portuguese regime, named Estado Novo, hosted its biggest national exhibition: the Exhibition of the Portuguese World (EPW). The event aimed both to commemorate Portuguese history and to justify the teleological nature of the dictatorship. This article discusses the national identity narrative conveyed by the allegorical pavilions conceived for the historical section of the EPW. In examining the ephemeral architecture and the debate which arose among intellectuals at the event, this article explores the process of narration and reinterpretation surrounding the display and elucidates the complex process of reception by the citizenry